Coupling of salting-out assisted liquid–liquid extraction with on-line stacking for the analysis of tyrosine kinase inhibitors in human plasma by capillary zone electrophoresis - Ahmed, Omar S.; Ladner, Yoann; Montels, Jérôme; Philibert, Laurent; Perrin, Catherine (Journal of Chromatography A, 2018)
•Extraction of tyrosine kinase inhibitors by salting-out liquid–liquid extraction.•Analysis of tyrosine kinase inhibitors by capillary electrophoresis technique.•In-line concentration by acetonitrile stacking at high sample volume injected. Developing an easy to use, cheap and fast analytical methodology is highly demanded for clinical practices, such as therapeutic drug monitoring (TDM). The present work deals with the development of an analytical methodology for the analysis of four basic anticancer drugs, namely tyrosine kinase inhibitors (TKIs), in human plasma by combining salting-out assisted liquid–liquid extraction (SALLE) with capillary electrophoresis (CE). This SALLE-CE methodology makes a full use of the advantages of both techniques by combining extraction, on-line concentration and separation in a simple way. First, plasma samples containing TKIs are mixed with acetonitrile (ACN) in appropriate volumes to precipitate proteins. After vortexing and centrifugation, sodium chloride (NaCl) is added to the plasma-ACN mixture to induce a two phases separation. TKIs are efficiently extracted (60–100% extraction efficiency) in the upper (mostly organic) phase which is directly analyzed by capillary electrophoresis (CE) coupled to UV detection. The high content of ACN in the upper phase allows the stacking of the analytes in the capillary (on-line stacking) during analysis. For the first time thanks to this electrophoretic process, the injected sample volume can be as large as 80% of the capillary volume (till the detector window). Good linearity was obtained for each TKI in the concentration range 60–2000 ng/ml with correlation coefficient (r²) between 0.997 and 0.999. LOD and LOQ in human plasma with such large injected volume were determined from 16 to 280 ng/ml and from 62 to 900 ng/ml respectively depending on the TKI. Recoveries for the four TKIs ranged from 60 to 100%. The repeatability of the SALLE-CE methodology for the analysis of TKIs in human plasma was evaluated with injected sample volume equal to 80% of the capillary volume till detector window. Relative standard deviations (RSDs) of less than 1.24 and 2.84% on migration times and corrected peak areas respectively were obtained at the LOQ. The sensitivity was enhanced by 61 to 265 folds confirming the applicability of the proposed methodology for the assay of TKIs in patients’ plasma.